Model Latihan Teknik Dasar Lari Sprint MAPHTRAS pada Atlet Lari Pemula - Fahmi, Azwan; Yunus, Moch. (Universitas Negeri Malang, 2020)
Abstract: Sprint Â is a fundamental technique in athletic sports. The aim of the researcher is to develop 7 models of sprint sprint technique. The research method used is research and development method. Procedure of development (1) needs analysis (2) product planning I (3) product evaluation I (4) product I (5) product trial I (6) product revision I (7) product II (8) trial II product (9) product II (10) product validation and report preparation. The test subjects used were 5 trainees for small group trials, and 10 trainees for large group trials on athlete-age athletes at the Puma Athletic Club of Batu City. The instruments used are questionnaires given to trainees. The results of this research and development are 7 models of sprint sprint training model, 1